Role of oxidative stress in impaired type II diabetic bone repair: scope for antioxidant therapy intervention? - Li, Pui; Alenazi, Kuraym Khalid Kuraym; Dally, Jordanna; Woods, Emma Louise; Waddington, Rachel Jane; Moseley, Ryan (Frontiers in Dental Medicine, 2024)
Impaired bone healing is a significant complication observed in individuals with type 2 diabetes mellitus (T2DM), leading to prolonged recovery, increased risk of complications, impaired quality of life, and increased risk of patient morbidity. Oxidative stress, resulting from an imbalance between the generation of reactive oxygen species (ROS) and cellular/tissue antioxidant defence mechanisms, has been identified as a critical contributor to the pathogenesis of impaired bone healing in T2DM. Antioxidants have shown promise in mitigating oxidative stress and promoting bone repair, particularly non-enzymic antioxidant entities. This comprehensive narrative review aims to explore the underlying mechanisms and intricate relationship between oxidative stress, impaired bone healing and T2DM, with a specific focus on the current preclinical and clinical evidence advocating the potential of antioxidant therapeutic interventions in improving bone healing outcomes in individuals with T2DM. From the ever-emerging evidence available, it is apparent that exogenously supplemented antioxidants, especially non-enzymic antioxidants, can ameliorate the detrimental effects of oxidative stress, inflammation, and impaired cellular function on bone healing processes during uncontrolled hyperglycaemia; and therefore, hold considerable promise as novel efficacious therapeutic entities. However, despite such conclusions, several important gaps in our knowledge remain to be addressed, including studies involving more sophisticated enzymic antioxidant-based delivery systems, further mechanistic studies into how these antioxidants exert their desirable reparative effects; and more extensive clinical trial studies into the optimisation of antioxidant therapy dosing, frequency, duration and their subsequent biodistribution and bioavailability. By enhancing our understanding of such crucial issues, we can fully exploit the oxidative stress-neutralising properties of these antioxidants to develop effective antioxidant interventions to mitigate impaired bone healing and reduce the associated complications in such T2DM patient populations.